Reversible tau hyperphosphorylation in hibernation : a blood biomarker and brain tissue study - Brum, Wagner S.; Montoliu-Gaya, Laia; Brinkmalm, Gunnar; Piotrowska, Diana; Camporesi, Elena; Jäger, Carsten; Isaksson, Helena S.; Martin, Sven; Kindberg, Jonas; Lantero-Rodriguez, Juan; Ferrari-Souza, João Pedro; Moscoso, Alexis; et al. (Acta Neuropathologica, 2025)
Tau hyperphosphorylation, a key neuropathological feature of tauopathies such as Alzheimer’s disease (AD), also occurs physiologically during mammalian hibernation and is fully reversed upon arousal, offering a unique translational model to study tau metabolism. However, limited data exist on insoluble and soluble tau alterations during hibernation and on patterns of tau fragment concentrations in the hibernating mammalian brain. We quantified tau biomarkers in plasma samples from ten free-ranging brown bears (Ursus arctos), captured during both their active summer period and hibernation in the winter, using clinically validated immunoassays and immunoprecipitation mass spectrometry (IP-MS) techniques. We also analyzed brain tissue from ten golden Syrian hamsters (Mesocricetus auratus) subjected to induced torpor (hibernation) versus euthermic (non-hibernating) states by quantifying multiple phosphorylated and non-phosphorylated tau peptides with an IP-MS method previously applied in human brain tissue. In brown bears, plasma levels of phosphorylated tau (p-tau) biomarkers p-tau181 and p-tau217 significantly increased during hibernation compared to summer (median increases of 362% and 294% by IP-MS, respectively), with similar increases found with immunoassays. Additional plasma p-tau biomarkers associated with AD pathology, including p-tau205 and p-tau231, were also increased during bear hibernation. In hamster brains, p-tau217, and p-tau231 were similarly elevated during torpor, while tau fragments from the microtubule-binding region (MTBR), associated with tangle aggregation, were not increased. In contrast, brain tissue from n = 10 AD patients, analyzed with the same IP-MS method, exhibited striking increases in p-tau (~ 50,000% for p-tau217) and MTBR fragments (~ 20,000% for MTBR tau354-369) compared with n = 10 human controls. We show that hibernation-linked tau hyperphosphorylation involves some of the same phospho-sites altered in AD, but occurs without MTBR tau aggregation. This highlights hibernation as a reversible, non-pathological model to study tau biology and mechanisms underlying AD due to its reversibility and lack of tau aggregation despite hyperphosphorylation in key AD tau phospho-sites.
Keywords: Alzheimer’s disease; Hibernation; Neuropathology; Phosphorylated tau; Plasma biomarkers; Tau; Tauopathies